Application of Anesthetics in Cancer Patients: Reviewing Current Existing Link With Tumor Recurrence - Liu, Xiaotian; Wang, Qian (Frontiers in Oncology, 2022)
Surgery remains the most effective cancer treatment, but residual disease in the form of scattered micro-metastases and tumor cells is usually unavoidable. Whether minimal residual disease results in clinical metastases is a function of host defense and tumor survival and growth. The much interesting intersection of anesthesiology and immunology has drawn increasing clinical interest, particularly, the existing concern of the possibility that the perioperative and intraoperative anesthetic care of the surgical oncology patient could meaningfully influence tumor recurrence. This paper examines current data, including recent large clinical trials to determine whether the current level of evidence warrants a change in practice. Available pieces of evidence from clinical studies are particularly limited, largely retrospective, smaller sample size, and often contradictory, causing several questions and providing few answers. Recent randomized controlled clinical trials, including the largest study (NCT00418457), report no difference in cancer recurrence between regional and general anesthesia after potentially curative surgery. Until further evidence strongly implicates anesthesia in future clinical trials, clinicians may continue to choose the optimum anesthetic-analgesic agents and techniques in consultation with their cancer patients, based on their expertise and current best practice.